Oestradiol as a neuromodulator of learning and memory - Taxier, Lisa R. (Nat Rev Neurosci, 2020)
Although hormones such as glucocorticoids have been broadly accepted in recent decades as general neuromodulators of memory processes, sex steroid hormones such as the potent oestrogen 17β-oestradiol have been less well recognized by the scientific community in this capacity. The predominance of female subjects in studies of oestradiol and memory, and the general (but erroneous) perception that oestrogens are ‘female’ hormones, have probably prevented oestradiol from being more widely considered as a key memory modulator in both sexes. Indeed, although considerable evidence supports a crucial role for oestradiol in regulating learning and memory in females, a growing body of literature indicates a similar role in males. This Review discusses the mechanisms of oestradiol signalling and provides an overview of oestradiol’s effects on spatial, object-recognition, social and fear memories. Although the primary focus is on data collected in females, effects of oestradiol on memory in males will be discussed, as will sex differences in the molecular mechanisms that regulate oestrogenic modulation of memory, which may have important implications for the development of future cognitive therapeutics.